Termorregulação e comportamento de ovinos Dorper X Santa Inês mantidos em diferentes sistemas de produção em clima subtropical - Czekoski, Zilmara Maria Welfer (2018)
The aim of this research is to evaluate whether the “silvipastoril” system interfere in the microclimate, thermoregulation and in the behavior of half-breed lambs Dorper X Santa Inês in a subtropical climate. This study was developed at the teaching unit research and extension of sheep and goat farming- UNEPE from Federal Technological University of Paraná, Câmpus Dois Vizinhos/ PR. The lambs were evaluated during the months of January and February of 2017, during 10 random days, in 2 breeding systems: “silvipastoril” (SSP) and full sun (PS). Each environment was composed by three repetitions and two animals per repetition, totaling 12 animals. They were also measured the following microclimatic variable: temperature and relative humidity of the air, velocity of the wind, surface temperature of the soil, and temperature of the black globe. From these variables, were calculated: temperature index of black globe (ITGU), thermal comfort index (ICT), radiant thermal charge (CTR) and specific enthalpy. To evaluate thermoregulation, the physiological variable measured were: rectal temperature (TR) average superficial temperature (TMS), respiratory frequency (FR) and cardiac frequency (FC). These variables research were assessed in the periods of morning and afternoon in the days on which the data were recorded. A day behavior was evaluated through an etogram composed by different behaviors. The behavioural studies happened from 7a.m. to 7 p.m.o'clock, together with several microclimatic variables, of different treatments. These ones were done in different days of thermoregulation evaluations. For statistical analysis of microclimatic data and the thermoregulation variables, it was adjusted to a mixed model and, subsequently they were subjected to the analysis of variance and Turkey test to the significance level of 5%. The animal behavior was analyzed by the Bayesian inference, with a model of mixed effects. The “silvipastoril” system attenuated the air temperature in relation to full sun (31.1 e 32 ºC), however, in the hottest time of the day the air temperature got above of thermal comfort zone for the lambs in both environments. There was a difference (P <0.05) among the treatments for the variable answers of FR and TR. The FR was of 98 and 128 mov. min.-1 for SSP and PS, respectively. And the TR was equal to 39.5 and 39.8 ºC, for SSP e PS. The CTR values differed between the shifts and treatments (P <0.05) and the SSP (542.9 W m-2) as the thermal maximum comfort environment in relation to PS (631.1 W m-2). For specific enthalpy (kJ kg dry air-1) there was a difference (P <0.05) between shifts for both treatments and also in the morning shift between SSP and PS (65.1 and 68.5 kJ dry kg-1). Related to the behaviour, the probability of grazing, lying idle time and walking were bigger to the animals presented in the SSP. In the PS, there was a major probability of standing idle time and drinking water in the hottest time of the day. The sheep breeding system influenced the microclimatic variables, thermoregulation answers and interfered in the behavior. This way the SSP provided an environment of greater thermal comfort for the lambs in relation to the PS.